2013
DOI: 10.1104/pp.113.224816
|View full text |Cite
|
Sign up to set email alerts
|

Stable Carbon Isotope Discrimination Is under Genetic Control in the C4 Species Maize with Several Genomic Regions Influencing Trait Expression  

Abstract: In plants with C 4 photosynthesis, physiological mechanisms underlying variation in stable carbon isotope discrimination (D 13 C) are largely unknown, and genetic components influencing D 13 C have not been described. We analyzed a maize (Zea mays) introgression library derived from two elite parents to investigate whether D 13C is under genetic control in this C 4 species. High-density genotyping with the Illumina MaizeSNP50 Bead Chip was used for a detailed structural characterization of 89 introgressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 60 publications
(88 reference statements)
0
37
0
Order By: Relevance
“…35 The relationships between these various environmental factors and modern C 3 plant δ 13 C values have been relatively well studied (e.g., 36,37 ), and some of that work has been in Africa, 38 but there have been fewer publications focusing on environmental variation in C 4 plants. Those C 4 plants that have received attention regarding environmentally driven isotopic variation have tended to be archaeologically and economically important species, such as maize, 39,40 sorghum, 41 and, more recently, foxtail millet (Setaria italica). 17,18 The standard carbon isotope model for C 3 plants 42 posits a negative correlation between plant δ 13 C values and water availability (e.g., precipitation, relative humidity)that is, an increase in precipitation will increase stomatal conductance and in turn decrease plant δ 13 C values.…”
Section: Carbon Isotopesmentioning
confidence: 99%
“…35 The relationships between these various environmental factors and modern C 3 plant δ 13 C values have been relatively well studied (e.g., 36,37 ), and some of that work has been in Africa, 38 but there have been fewer publications focusing on environmental variation in C 4 plants. Those C 4 plants that have received attention regarding environmentally driven isotopic variation have tended to be archaeologically and economically important species, such as maize, 39,40 sorghum, 41 and, more recently, foxtail millet (Setaria italica). 17,18 The standard carbon isotope model for C 3 plants 42 posits a negative correlation between plant δ 13 C values and water availability (e.g., precipitation, relative humidity)that is, an increase in precipitation will increase stomatal conductance and in turn decrease plant δ 13 C values.…”
Section: Carbon Isotopesmentioning
confidence: 99%
“…Similar to the application of Δ to quantify WUE i of C 3 plants (Farquhar and Richards, 1984; Yang et al , 2016 b ), Δ was suggested as a potentially promising screening tool for breeding and improvement of C 4 crops (Henderson et al , 1998; Gresset et al , 2014; von Caemmerer et al , 2014). However, such endeavours require knowledge of the magnitude and variability of ϕ and relevant environmental drivers.…”
Section: Introductionmentioning
confidence: 99%
“…Water saving due to higher intrinsic water-use efficiency has been popularised in breeding research with the introduction of carbon isotope discrimination (CID) as an easily measurable parameter in the mid-1980s (Farquhar and Richards 1984). CID has been assessed for various crops such as C 3 cereals (Araus et al 2002), maize (Gresset et al 2014), soybean (Gitz et al 2005), sorghum (Henderson et al 1998), faba bean (Link et al 2007) and others. CID is an indicator of conservative water use and related to earliness.…”
Section: Breeding For Dehydration Avoidancementioning
confidence: 99%